(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
For some time before the COVID-19 pandemic, borders seemed to lose importance, although it was still clear that the world remained highly bordered. In Europe, the reestablishment of strict border controls in response to the pandemic resulted in increased pressures on the environment, the resurgence of global neo-imperialism, and stricter governance of energy resources. The object of this chapter is to explore the historic entanglement between the environment and international border-making by examining the strategies used to bring order to these frontier zones—a process I call “(b)order-making.” The chapter is based on research on Karelia, a North-Western borderland between the European Union and Russia. Of current geopolitical significance to Finland, Sweden, and Russia, Karelia has constituted a complex space where geopolitical considerations have prevailed over environmental concerns.